Understanding the management of pediatric spondylodiscitis based on existing literature; a systematic review - Narges Lashkarbolouk; Mahdi Mazandarani; Brice Ilharreborde; Mohammad Hossein Nabian (BMC Pediatrics, 2023)
Abstract Background Spondylodiscitis (SD), a rare disease in children, poses diagnostic challenges due to non-specific presenting symptoms, scarcity in incidence, and difficulty expressing pain in non-verbal children. Method A comprehensive search was conducted on three databases, including PubMed/Medline, Web of Science, and Scopus until March 2023. The inclusion criteria were studies that investigated the clinical characteristics, treatment, and complications of children’s spondylodiscitis. Full text of cross-sectional and cohort studies were added. The quality assessment of cohort studies was conducted using the Newcastle-Ottawa Quality Assessment Scale. The search, screening, and data extraction were performed by two researchers independently. Result Clinical manifestations of discitis in children are nonspecific, such as back pain, fever, reduced ability or inability to walk or sit, limping, and reduced range of movements. The mean delay in the time of diagnosis was 4.8 weeks. The most affected site of all the studies was the lumbar spine. 94% of studies reported increased inflammatory markers such as white blood cell count, C-reactive protein, and erythrocyte sedimentation rate. Less than 30% of patients had positive blood cultures and biopsy findings. The most common microbiological results (64%) were Staphylococcus Aureus and Kingella kingae. In radiographic evaluation, intervertebral disk narrowing, lumbar lordosis reduction, loss of disk height, and destruction of the vertebral body have been reported. In all studies, antibiotic therapy was initiated; in 52% immobilization was employed, and 29% of studies reported surgery was performed, and the follow-up period differed from 1.5 months to 156 months. 94% of studies reported complications such as vertebral body destruction, back pain, kyphosis, reduced range of movement, scoliosis, and neurological complications. Conclusion Spondylodiscitis is an uncommon, heterogeneous, multifactorial disease with resulting difficult and delayed diagnosis. Due to its morbidity, it is essential to investigate children with refusal to walk, gait disturbances, or back pain, particularly when associated with elevated inflammatory markers.